The impact of assisted living facilities on hospitalization, length of stay, and mortality rates among the elderly: A systematic review and meta-analysis - Sopacua, Andre; Haryanto, Ahmad; Soenarti, Sri (Deka in Medicine, 2025)
BACKGROUND: With 21.3% of the global population aging, the demand for assisted living facilities (ALFs) for individuals with complex medical conditions has surged. However, residing in ALFs may be associated with higher hospital admission rates, longer hospital stays, and increased mortality compared to living at home. The exact relationship between ALFs and these adverse health outcomes remains unclear. OBJECTIVES: To determine the correlation between ALFs—including nursing homes (NH), home care (HC), and residential care (RC)—and hospitalization rates, length of hospital stay, and mortality compared to community-dwelling individuals. METHODS: A literature search was conducted across five databases, focusing on risk ratios for hospitalization and mortality, as well as mean changes in hospital duration. This study compared interventions involving NH, HC, and RC with community dwelling. Quality appraisal was performed using the Newcastle-Ottawa Scale (NOS), and a forest plot was generated using a random-effects model with 95% confidence intervals (CI). RESULTS: Community-dwelling individuals had a 1.21 times higher likelihood of hospitalization compared to those in ALFs (RR 1.21, 95% CI: 0.97–1.51, I²=100%, p=0.10). Subgroup analysis showed that individuals receiving HC and NH had lower hospitalization rates than those in community settings, while RC residents had a higher risk. Additionally, ALF residents experienced longer hospital stays compared to the control group [MD: -1.21 (95% CI: -3.06 to 0.65, I²=99%, p=0.20)]. Mortality rates were 2.83 times higher among community dwellers than ALF residents (RR 2.83, 95% CI: 1.43–5.61, I²=100%, p=0.003). Subgroup analysis also indicated lower mortality risks among individuals receiving RC, NH, and HC compared to those in community settings. CONCLUSION: ALFs are associated with an increased risk of hospitalization and mortality, as well as a shorter length of hospital stay.